Latent structure indicators for assessing feautres of young sportsmen coaches - Radevic, N.; Bajric, O.; Božic, I. (Sports Science and Health, 2016)
Research was conducted on a sample of 121 respondents in total-sportsmen aged 14-16 years old from five different sports (skiing, boxing, swimming, volleyball and basketball), trough a questionnaire containing 19 representative indicators - qualities that the coach should possess. Examined are the attitudes of young and promising sportsmen of the desirable characteristics of a good coach. It`s about the selected young and promising sportsmen, whose quality is determined on the basis of achieved results at official championships in of Republic of Srpska, Bosnia and Herzegovina and international competitions. The survey questionnaire was administered in which any claim has 5 replies as follows: always, often, sometimes, rarely did I ever. It`s about five-point Liker scale. The survey contains questions related to gender, length of training period and type of sport. In order to determine the latent structure of the appropriateness of indicators was used factor analysis with Varimax rotation in solution. Given results of the factor analysis with Varimax rotation in solutions showed stable set of four isolated latent dimensions that can be described as: (1) technical quality of the trainers (2) the general human traits coaches (3) external characteristics of trainers and (4) the ratio of coaches to the sportsmen. The results point to the fact that the qualities that a coach has to exhibit the work of young and promising sportsmen in training and competition is of great importance for the formation of the whole personality and versatile young sportsmen in his sport promotion.